2014
DOI: 10.1590/s0100-69912014000300004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bariatric surgery on depression and anxiety symptons, bulimic behaviors and quality of life

Abstract: a decrease in psychiatric symptoms was observed after bariatric surgery, as well as the reduction in the use of psychoactive substances. In addition, there was an improvement in quality of life after surgical treatment of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
1
10
1
6
Order By: Relevance
“…They found that 10 patients (28.6%) quit after the surgery, but 7 nonsmokers (12.1%) started smoking. Lent et al (2013) found that older adults were more likely to reduce smoking than young adults postoperatively (p=.002) and that there was no significant change of smoking from pre (19.4%) to post- (14.8%) surgery, which was consistent with findings in Tae et al (2014). However, they also found that 63.3% of 30 preoperative smokers quit after surgery and 9.6% of 125 non-smokers reported initiation of smoking after surgery.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…They found that 10 patients (28.6%) quit after the surgery, but 7 nonsmokers (12.1%) started smoking. Lent et al (2013) found that older adults were more likely to reduce smoking than young adults postoperatively (p=.002) and that there was no significant change of smoking from pre (19.4%) to post- (14.8%) surgery, which was consistent with findings in Tae et al (2014). However, they also found that 63.3% of 30 preoperative smokers quit after surgery and 9.6% of 125 non-smokers reported initiation of smoking after surgery.…”
Section: Resultssupporting
confidence: 65%
“…A “J”-shape curve trajectory of composite substance use scores over time after surgery was proposed (Conason et al, 2013), indicating an immediate decline from baseline (pre-surgery) to 1 month after surgery and then a significant increase after 1 month postoperatively. The time-related pattern was not observed on cigarette smoking or recreational drug use, while an increase in alcohol use prevalence was not consistent across studies (King et al, 2012; Tae et al, 2014). …”
Section: Discussionmentioning
confidence: 74%
“…Seventeen out of these 19 studies reported a reduction in depression symptoms from presurgery, but two studies found that depression symptoms remained the same from 6‐month follow‐up . One of these studies collected their data between 6 and 10 months post‐surgery and found that pre‐surgery depression symptoms reduced from 78% to 44% . Two of these studies used clinical assessments and found an overall reduction of people with depression, whereas one did not .…”
Section: Resultsmentioning
confidence: 99%
“…There were nine studies that collected their follow‐up data at around 12 months post‐surgery. Seven out of these nine studies reported a reduction in anxiety symptoms from pre‐surgery, but two studies found that pre‐surgery anxiety symptoms stayed the same at 12‐month follow‐up . One study collected their data between 6 and 10 months post‐surgery and found that pre‐surgery anxiety symptoms reduced from 87% to 57% .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation